The elements of environment: an analysis from the spiritual perspectives - Noor Shakirah bt Mat Akhir; Muhammad Azizan Bin Sabjan (Environmental Management Society, Malaysia, 2011)
The elements of environment are mentioned many times in the Quran. These elements such as mountain, water, tree sea, sky, earth and their roles lucidly exhibited in the Quran. Presently , the environment is facing assorted threats and varios steps have been taken to outmanoeuvre these menaces. Despite many strategies taken to sustain the environment, there is one step which is often being neglected and that is to dissolve the threats and retain the environment via spiritual aspects.This paper attemps to exhibit the connection between the elements of environment and the spiritual aspects as portrayed in the Quran.It is hoped that the paper will provide a clearer understanding of the connection between spiritual aspects and the preservation of environmentand how the environment can be sustained via spiritual realizations.